THE USE OF INSTANT MESSAGING BY EMPLOYEES AT COLLEGES IN PEKANBARU - Hartati, Seri; Rahmalina, Widdya; Arisandi, Diki (PEOPLE: International Journal of Social Sciences, 2018)
Instant Messaging (IM) now become one of the common communication tool used for personal activities and corporate needs. According to survey results from eMarketer reports, instant messaging users in Indonesia in 2014 was 37.6 million users, increased in 2015 as much as 52.9 million users, 2016 as many as 62.6 million users and predicted to continue to improve in 2017 (72, 5 million users), 2018 (81.7 million) and 2019 as many as 91.6 million users. This number shows increasing use of IM continuously. Although some research suggests that using IM may interfere with the work activity, but in recent years research has increased IM usage in the workplace. The application of IM by employees in college affects their performance in daily activities. Therefore the use of IM requires proper management to maximize its benefits. Using this IM technology allows sharing information quickly, precisely and accurately; so that will improve the effectiveness of employee performance. This research was using a qualitative method, by testing the influence of independent variable to dependent variable. Through this research is expected to contribute the use of IM, so that the college can provide more specific management services for employees. Hopefully, could support the creation of e-management and E-education as the power of the smart city in Pekanbaru.